Genomic analysis of a Streptococcus pyogenes strain causing endocarditis in a child. (May 2017) - Beye, M.; El Karkouri, K.; Labas, N.; Raoult, D.; Fournier, P.-E.
Abstract: We sequenced the genome of Streptococcus pyogenes strain G773 that caused an infective endocarditis in a 4-year-old boy suffering from acute endocarditis. The 1.9-Mb genome exhibited a specific combination of virulence factors including a complete integrative and conjugative element, sp2905, previously described as incomplete in S . pyogenes, and five bacteriocin-coding genes. However, strain G773 lacked a CRISPR-Cas system.